Development and Validation of Perception of Wisdom Exploratory Rating Scale: An Instrument to Examine Teachers' Perceptions of Wisdom - Sareh Karami; Andy Parra-Martinez; Mehdi Ghahremani; Marcia Gentry (MDPI AG, 2024)
The purpose of this study was to develop and validate the Perception of Wisdom Exploratory Rating Scale based on the Polyhedron Model of Wisdom (PMW). A total number of 585 responses from in-service and preservice teachers was collected. In the EFA, the items fit a seven-factor structure, producing the following subscales: knowledge management, self-regulation, moral maturity, openness, tolerance, sound judgment, and creative thinking. CFA was performed to test the construct validity of the scale. The model produced a good fit to the data (χ2/df = 1.67, CFI = 0.92, TLI = 0.91, RMSEA = 0.049, and SRMR = 0.06). With continued testing and revisions, this instrument could be useful for the cross-cultural comparison of perceptions of wisdom and identification of barriers to promoting wisdom instruction.